2017
DOI: 10.1371/journal.pone.0184301
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography of the peripapillary capillaries in primary open-angle and normal-tension glaucoma

Abstract: ObjectivesTo evaluate the vascular architecture of the radial peripapillary capillaries (RPCs) and its relation with visual function in patients with open-angle glaucoma (OAG) and normal-tension glaucoma using spectral-domain optical coherence tomography (SD-OCT) angiography.Subjects and methodsClear OCT angiography images of blood vessels in the optic disc and peripapillary retina were obtained from 52 patients (52 eyes) aged 55.42±10.64 (range 28–72) years with primary OAG. The mean spherical equivalent was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 19 publications
2
19
0
3
Order By: Relevance
“…26,27 Global NFL thickness was also correlated with the global VD and PD as shown in many studies. 28,29 Although this correlation showed a reduced PD with increasing tissue loss and progressing disease, the reduced perfusion as a cause of the tissue loss and reduction of NFL thickness still cannot be ruled out. The NFL correlated inversely with the venous O2S and directly with the AV-D, which has been previously reported.…”
Section: Discussionmentioning
confidence: 91%
“…26,27 Global NFL thickness was also correlated with the global VD and PD as shown in many studies. 28,29 Although this correlation showed a reduced PD with increasing tissue loss and progressing disease, the reduced perfusion as a cause of the tissue loss and reduction of NFL thickness still cannot be ruled out. The NFL correlated inversely with the venous O2S and directly with the AV-D, which has been previously reported.…”
Section: Discussionmentioning
confidence: 91%
“…Bojikian et al investigated optic disc perfusion differences in healthy subjects, POAG, and NTG and showed that optic disc perfusion was significantly reduced in POAG and NTG groups compared to normal controls, but no difference was seen between POAG and NTG groups with similar levels of VF damage [ 20 ]. Igarashi et al published that flow density and the disappearance angle of the radial peripapillary capillaries were significantly and independently correlated with glaucoma-related functional and morphological changes in the optic nerve in POAG and NTG [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…While comparing OCTA examination to traditional methods, previous studies have demonstrated that OCTA is a reliable tool for the analysis of retinal vasculature, similar to fluorescein angiography [21, 22], and that the retinal vasculature layers can be imaged more precisely compared to fluorescein angiography and indocyanine green angiography [23, 24]. With regard to glaucoma, HTG, after evaluation by OCTA, showed decreased peripapillary vessels that correlate with the RNFL and VF defects and impaired macular VD [9, 14, 17, 18, 25-28], while the OCTA evaluation in NTG subjects showed similar results and precision in the peripapillary and macular vasculature [10, 15, 17, 18, 29]. In addition, the spilt-layer function of OCTA can appropriately separate the different retinal layers and analyze each vasculature in more detail than the traditional approach [4].…”
Section: Discussionmentioning
confidence: 99%
“…Although a correlation was found between declined peripapillary and macular VD and structural and functional parameters in HTG and NTG patients [10, 15-18], whether lower macular VD precedes or follows glaucoma development is still unclear. Additionally, while previous research has revealed a decrease in total VD [15], vascular alteration in different macular layers has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%